Tinjauan Yuridis tentang Pengaturan dan Perlindungan Hak Konsumen terhadap Perjanjian Perdagangan Bebas di Indonesia - Siti Syaidah; Mela Nur Annisa; Rencyka Andieni; Nadia Rahmania; Farahdinny Siswajanthy (Sharia Journal and Education Center Publishing, 2024)
This journal discusses the legal review of cases of protection of rules and regulations. The existence of this journal is formed with the aim of evaluating the effectiveness of consumer rights in free trade agreements in Indonesia. Then this journal also examines the laws and regulations on consumer rights in free trade in Indonesia, which are based on definitions, objectives, legal reviews, and legal protection and issues. Our journal research uses normative legal research methods or techniques where this research is conducted with a study using legal materials, namely laws and other legal regulations and secondary legal materials, namely research journals.